2023
DOI: 10.3389/fonc.2023.1077922
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of trends in gut microbiome associated with colorectal cancer using machine learning

Abstract: BackgroundThe rapid growth of publications on the gut microbiome and colorectal cancer (CRC) makes it feasible for text mining and bibliometric analysis.MethodsPublications were retrieved from the Web of Science. Bioinformatics analysis was performed, and a machine learning-based Latent Dirichlet Allocation (LDA) model was used to identify the subfield research topics.ResultsA total of 5,696 publications related to the gut microbiome and CRC were retrieved from the Web of Science Core Collection from 2000 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Furthermore, this has also attracted some researchers to conduct a comprehensive assessment in this research field. A recently published study examined up to 5,696 publications, and a bibliometric analysis found that "microbiome sequencing and tumor"; "microbiome compositions, interactions, and treatment"; "microbiome molecular features and mechanisms"; and "microbiome and metabolism" were the most intensively researched topics in the field of the gut microbiome in CRC research (29). Wu W (30) et al also investigated the research trends in the relationship between the gut microbiome and CRC research; they found that "Gut Microbiota," "Colorectal Cancer," "Inflammation," "Probiotic," and so forth were the most frequent, and they revealed the current hotspots and trends in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this has also attracted some researchers to conduct a comprehensive assessment in this research field. A recently published study examined up to 5,696 publications, and a bibliometric analysis found that "microbiome sequencing and tumor"; "microbiome compositions, interactions, and treatment"; "microbiome molecular features and mechanisms"; and "microbiome and metabolism" were the most intensively researched topics in the field of the gut microbiome in CRC research (29). Wu W (30) et al also investigated the research trends in the relationship between the gut microbiome and CRC research; they found that "Gut Microbiota," "Colorectal Cancer," "Inflammation," "Probiotic," and so forth were the most frequent, and they revealed the current hotspots and trends in this field.…”
Section: Discussionmentioning
confidence: 99%